FACTORS THAT INFLUENCE THE BUYING DECISION OF SECOND-HAND CLOTHES: EVIDENCE IN THAILAND - Santang, Laongdao; SUBONGKOD, Mallika (Asian Administration and Management Review, 2023)
As second-hand clothes are one of the most popular items, the competition is quite intense. The objective of this research was to study marketing mix factors and factors of product trust influencing the buying decision of second-hand clothes. The data were collected from the samples of 400 buyers of second-hand clothes in Chumphon Province, Thailand, using the questionnaire as the research tool. The data were analyzed using percentage, mean, standard deviation, and multiple regression analysis. The research results revealed that the marketing mix factors consisted of the product, place, promotion, people, physical evidence, and process. The factors of product trust consisted of quality, image, and brand. These influence the buying decision of second-hand clothes of the sample group with statistical significance at the 0.05 level. Therefore, entrepreneurs should pay great attention to such factors.